(untitled) (Mustansiria Dental Journal, 2018)
Forty five mesial canals of extracted human mandibular molars were instrumented with ProFile ISO .06 nickel-titanium rotary instruments and obturated with lateral condensation using three different master cones: .06 tapered gutta-percha cone (group I), .04 tapered gutta-percha cone (group II), .02 tapered gutta-percha cone (group III). Zinc oxide eugenol sealer was used in all groups. After 48 hours in an incubator, the roots were coated with nail polish and were the submerged in methylene blue dye for 72 hours. The roots were then split longitudinally and the apical leakage measured and compared for each group. Although there was no statistical significant difference among groups (P>0.05), group (I) with .06 tapered gutta-percha master cone showed the lowest mean of dye penetration.